Characterisation of highly radiating neon seeded plasmas in JET-ILW. (14th October 2019) - Glöggler, S.; Wischmeier, M.; Fable, E.; Solano, E.R.; Sertoli, M.; Bernert, M.; Calabrò, G.; Chernyshova, M.; Huber, A.; Kowalska-Strzęciwilk, E.; Lowry, C.; de la Luna, E.; et al.
Abstract: To study the impact of strong impurity radiation on the energy confinement and the discharge stability at JET-ILW, dedicated high-density, highly heated experiments with neon seeding have been performed. In these experiments an increase of radiation in the core and especially the pedestal region plus a characteristic strong X-point radiator inside the confined region have been observed. The increased radiation inside the separatrix had no impact on the energy confinement. Only at the highest neon puff rates and highest heating powers ( ) a weak H-mode without back-transitions to L-mode (M-mode) could be achieved, while at lower heating powers or seeding levels L-modes and oscillations between H-mode and L-mode could be observed. In H-mode, at highest neon seeding levels the targets are in complete detachment. A degradation of the pedestal density profile was observed when neon was seeded. A correlation between this density pedestal degradation, the appearance of an X-point radiator and the detachment of the targets was found in neon seeded H-mode pulses. In ASTRA-TGLF core transport simulations it could be shown that the increase of the electron temperature in the core with neon seeding is attributed to a partial stabilisation of ion temperature gradient modes.